Long-term outcomes of LDR-brachytherapy for localized prostate cancer - Lauri Mäkelä; Anssi Pétas; Arto Mikkola; Harri Visapää (Frontiers in Oncology)
IntroductionThis retrospective study aims to evaluate the long-term efficacy and urinary toxicity of LDR-brachytherapy for localized prostate cancer.Materials and methods235 primary prostate cancer patients treated with LDR-brachytherapy and subsequently followed up in our center were included in this study. Biochemical relapse free survival (bRFS), overall survival (OS), and cancer-specific survival (CSS) were evaluated. Additionally, the incidence of late urinary complications was recorded.ResultsMedian follow-up time was 11,6 years. 181 patients (77%) were classified as low-risk patients, while 52 patients (22,1%) were intermediate risk. The overall bRFS was 83,8% at 5 years and 72,4% at 10 years. 5- and 10-year OS were 97,8% and 87,8% respectively. There was no statistically significant difference in bRFS or OS between different risk groups. The rate of late urinary complications was 8,9%. Volume of prostate had a statistically significant effect on bRFS, as smaller prostate volumes led to worse bRFS.ConclusionsThis retrospective study shows that LDR brachytherapy is an effective treatment for low- and intermediate risk prostate cancer patients with relatively low but still significant risk of late urinary complications.